أثر الفساد الإداري والمالي في زيادة البطالة - ملوكي، أوس (جامعة الوادي University of Eloued, 2025)
تهدف هذه الدراسة لتوضيح أثر الفساد الإداري والمالي في زيادة البطالة، مستعرضين مفهوم البطالة، وعلاقة البطالة ببعض المتغيرات الاقتصادية، ومفهوم الفساد، وقياس الفساد حسب منظمة الشفافية الدولية، وأسباب الفساد، واثأر الفساد. وتم اتباع المنهج الوصفي، ومن بين نتائج الدراسة للبطالة علاقة ببعض بالمتغيرات الاقتصادية ومن بينهم النمو الاقتصادي والتضخم، تعتمد منظمة الشفافية الدولية في قياس الفساد على مؤشر مدركات الفساد، ومؤشر دافعي الرشوة، ومؤشر الفساد العالمي. ومن بين توصيات الدراسة ضرورة التركيز على القطاع الصناعي والفلاحي من أجل إنقاص البطالة خصوصا وأن هذين القطاعين بإمكانهما استقطاب أكبر عدد من العمال. This study aims to clarify the impact of administrative and financial corruption on increasing unemployment, reviewing the concept of unemployment, the relationship of unemployment to some economic variables, the concept of corruption, and measuring corruption according to Transparency International, the causes of corruption, and the impact of corruption. The descriptive approach was followed, and among the results of the study of unemployment are related to some economic variables, including economic growth and inflation, Transparency International depends on measuring corruption on the Corruption Perceptions Index, the Corruption Payers Index and the Global Corruption Index. Among the recommendations of the study is the necessity to focus on the industrial and agricultural sectors in order to reduce unemployment, especially as these two sectors can employ the largest number of workers,
The impact of administrative and financial corruption on increasing unemployment
Keywords: الفساد الإداري; المالي; والبطالة; administrative and financial corruption; and unemployment